Non-transparent quartz glass and preparation method thereof
By controlling the heating rate and atmosphere pressure in quartz sand through induction heating method, the uniformity and purity of opaque quartz glass bubbles in the prior art are solved, and efficient and low-cost preparation is achieved, and it is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411348905.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-26
AI Technical Summary
In the existing preparation methods for opaque quartz glass, it is difficult to evenly distribute micron-level bubbles, resulting in poor mechanical strength and light-shielding performance, high preparation cost and low purity, and impurities are introduced in sintering of hydrogen and oxygen flames, increasing the hydroxyl content.
By controlling the atmosphere pressure and heating rate in the induction heating furnace, the preheating and melting process of quartz sand is controlled, ensuring that the bubbles are formed into a spherical shape, adjusting the bubble diameter and quantity, achieving density adjustment, reducing energy consumption and production cost.
It has achieved good thermal insulation performance, low impurity content, low production cost, and adjustable product density. It is suitable for semiconductor and biomedical fields, improving mechanical strength and light shading performance.
Smart Images

Figure CN119241046A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of opaque quartz glass, and in particular to a preparation method of opaque quartz glass and a product thereof. Background Art
[0002] Due to its unique physical and chemical properties, such as high temperature resistance, ablation resistance, and electrical insulation, quartz glass is widely used in semiconductors, aerospace, optical communications, photovoltaics, biomedicine, and electronics.
[0003] Glass with a large number of micron-sized bubbles evenly distributed in quartz glass is called opaque quartz glass. Opaque quartz glass not only has outstanding performances of ordinary quartz glass in terms of purity, thermals, and chemical corrosion resistance, but also has unique thermal insulation properties. In semiconductor, photovoltaic and other manufacturing equipment, it is used for heating components such as flanges and furnace core tubes to increase the scattering of thermal radiation inside the material and effectively prevent heat loss; opaque quartz glass has strong light-shielding properties and can be used as a reflector substrate for projector light sources. In addition, opaque quartz glass with high chemical stability has the potential to be used in the field of biological implants, by regulating its density and pore size to simulate the stiffness and strength of human bones.
[0004] The preparation of opaque quartz glass is mainly achieved through the following methods:
[0005] 1. Adding a small amount of inorganic or organic pore-forming agent (such as silicon nitride, carbon powder, polysiloxane and white carbon black, polystyrene powder) to the quartz sand raw material, and melting the mixed raw material using an oxyhydrogen flame (for example, Patent Documents 1 to 3). However, this method not only reduces the purity of the product, but also has a high preparation cost. At the same time, the pore-forming powder is easy to agglomerate and cannot be fully and evenly mixed with the quartz sand, resulting in large pore diameters, poor mechanical strength and light-shielding properties.
[0006] 2. After the quartz sand raw material is crushed, ball-milled, and wet-granulated, hydrogen-oxygen flame or vacuum melting is adopted (for example, Patent Document 4). However, wet granulation will introduce a large amount of impurities during the preparation process, resulting in a high hydroxyl content in the product.
[0007] 3. Without adding a foaming agent, the heat treatment is interrupted before the quartz sand is completely densified, and partial sintering is performed (for example, Patent Document 5). However, interrupting the heat treatment makes it difficult to form spherical bubbles, which reduces the mechanical strength of the product.
[0008] Existing patent technology literature:
[0009] Patent document 1: Japanese Patent No. 3043032;
[0010] Patent document 2: Japanese Patent No. 6666464;
[0011] Patent document 3: Japanese Patent No. 6676826;
[0012] Patent document 4: CN116648436A;
[0013] Patent document 5: Japanese Patent No. 3394323. Summary of the invention
[0014] The present invention provides an opaque quartz glass and a preparation method thereof. The preparation method of the present invention is an induction heating method. The density and the size and number of bubbles of the opaque quartz glass product can be regulated over a wide range by the preparation method of the present invention. The obtained opaque quartz glass has the advantages of good heat insulation performance, low production cost, and low hydroxyl and impurity content. The preparation method has the characteristics of short time consumption and low energy consumption.
[0015] [1] A method for preparing opaque quartz glass, comprising:
[0016] An induction heating furnace is used, the atmosphere in the furnace is a protective atmosphere that does not participate in the reaction, and the pressure of the protective atmosphere is 10000-90000Pa, such as 20000Pa, 35000Pa, 45000Pa, 50000Pa, 55000Pa, 60000Pa, 75000Pa, etc.;
[0017] The quartz sand is placed in the induction heating furnace, and the temperature is first raised to 1400-1570°C (for example, 1400°C, 1480°C, 1490°C, 1510°C, 1500°C, etc., close to the β-quartz transition temperature) to preheat the quartz sand; then the temperature is raised to 1650-1710°C (for example, 1680°C, 1690°C, etc.) at a rate not exceeding 0.2°C / s (for example, 0.002°C / s, 0.005°C / s, 0.041°C / s, 0.042°C / s, 0.052°C / s, 0.067°C / s, 0.19°C / s, etc.) , 1700°C, etc.) to uniformly heat the quartz sand; then raise the temperature to 1740-1900°C (e.g. 1750°C, 1760°C, etc.) at a rate of not less than 0.2°C / s (e.g. 0.27°C / s, 0.33°C / s, 0.30°C / s, 0.40°C / s, 0.45°C / s, 0.50°C / s, 1°C / s, etc.) to make the quartz sand reach the melting temperature and sinter; finally cool down at a rate not exceeding 2°C / s (e.g. 0.7°C / s, 0.9°C / s, 1°C / s, 1.2°C / s, etc.) to obtain opaque quartz glass.
[0018] The present invention adopts a relatively low pressure (10000-90000 Pa) instead of a vacuum, so that the bubbles in the glass can be always kept.
[0019] The preparation method of the present invention slows down the heating rate before the quartz glass forming temperature and speeds up the heating rate after the quartz sand particles are fully preheated, so as to achieve uniform heating and spherical growth of bubbles. By adjusting the heating curve, the bubble diameter and the number of bubbles can be controlled, thereby achieving the purpose of density regulation.
[0020] Specifically, the present invention slowly heats up to 1650-1710°C in order to make the quartz sand transfer heat evenly. In this process, the quartz sand reaches the critical point of melting but always remains in an unmelted state; and then quickly heats up to 1740-1900°C because, at a temperature of 1740-1900°C, the quartz sand melts and begins to sink and densify. The fast heating rate is to retain as many of these interstitial bubbles as possible to prevent them from escaping (they are wrapped in the glass solution before escaping). If the heating rate is slow, many bubbles will be expelled by the sinking glass solution. If the heating rate is fast and the viscosity of the quartz is high, the bubbles will not have time to be discharged.
[0021] In some embodiments, in the method for preparing the opaque quartz glass described in [1], the protective atmosphere may include a nitrogen atmosphere and / or a rare gas (such as helium and / or argon) atmosphere.
[0022] In some embodiments, in the method for preparing the opaque quartz glass described in [1], the total heating time may not exceed 5 hours.
[0023] In some embodiments, in the method for preparing the opaque quartz glass described in [1], the quartz sand may be dried before being placed in the induction heating furnace.
[0024] In some embodiments, in the method for preparing the opaque quartz glass described in [1], the quartz sand may be subjected to ultrasonic and / or vibration operations before being placed in the induction heating furnace, so that the quartz sand is densely packed without gaps generated by "bridging" in the middle, which is beneficial to avoid excessive bubble size in the final opaque quartz glass product.
[0025] In some embodiments, in the method for preparing opaque quartz glass described in [1], the size of the quartz sand placed in the induction heating furnace is 40-200 mesh, such as 80-100 mesh, 80-120 mesh, 80-200 mesh, 120-200 mesh, 40-80 mesh, 180-200 mesh, etc. When the quartz sand of the above mesh sizes is piled up, there are certain gaps inside, and these gaps will be converted into bubbles of the required size during the sintering process.
[0026] In the preparation method of the present invention, after the quartz sand is placed in the induction heating furnace, it is first heated to 1400-1570° C. During the heating process at this stage, the terminal temperature of the heating will affect the maximum size of the bubbles in the final opaque quartz glass product. The higher the terminal temperature, the smaller the maximum size of the bubbles in the opaque quartz glass product, and the lower the terminal temperature, the larger the maximum size of the bubbles in the opaque quartz glass product.
[0027] In some embodiments, in the method for preparing opaque quartz glass described in [1], after the quartz sand is placed in the induction heating furnace, the temperature can be first raised to 1400-1570°C at a rate of not less than 0.3°C / s (e.g., 0.4°C / s, 0.48°C / s, 0.49°C / s, 0.5°C / s, 0.51°C / s, 0.6°C / s, 0.8°C / s, 1°C / s, etc.) to preheat the quartz sand.
[0028] In some embodiments, the method for preparing the opaque quartz glass described in [1] can preheat the quartz sand by keeping the temperature at 1400-1570° C. for 3-30 min (e.g., 5 min, 8 min, 10 min, 15 min, etc.).
[0029] In some embodiments, in the method for preparing opaque quartz glass described in [1], after the quartz sand is placed in the induction heating furnace, it can be heated to 1000°C at a rate of not less than 0.3°C / s (e.g., 0.5°C / s, 0.8°C / s, 1°C / s, etc.), and kept warm for 5 to 30 minutes (e.g., 10 minutes, 20 minutes, etc.), and then heated to 14400 to 1570°C at a rate of 0.3 to 0.6°C / s (e.g., 0.4°C / s, 0.48°C / s, 0.49°C / s, 0.5°C / s, 0.51°C / s, 0.6°C / s, etc.), and kept warm for 3 to 30 minutes to preheat the quartz sand. Furthermore, in the process of heating to 1000°C, multiple temperature rising gradients can be set, for example, staying at one or more temperature points for a period of time independently, and then continuing to heat.
[0030] In the preparation method of the present invention, during the stage of heating to 1650-1710° C., the terminal temperature of the heating also affects the maximum size of bubbles in the final opaque quartz glass product. The higher the terminal temperature, the larger the maximum size of bubbles in the opaque quartz glass product, and the lower the terminal temperature, the smaller the maximum size of bubbles in the opaque quartz glass product.
[0031] In some embodiments, the method for preparing the opaque quartz glass described in [1] can heat the temperature to 1650-1710°C at a rate of 0.002-0.2°C / s, so that the quartz sand is evenly heated.
[0032] In the preparation method of the present invention, during the stage of heating to 1740-1900°C, the heating rate will affect the density of the final opaque quartz glass. The faster the heating rate, the smaller the density of the final opaque quartz glass, and the slower the heating rate, the greater the density of the final opaque quartz glass. In the preparation method of the present invention, the heating rate during the stage of heating to 1740-1900°C is preferably not less than 0.2°C / s, and further preferably 0.2-1°C / s.
[0033] In the preparation method of the present invention, after the temperature is raised to 1740-1900°C, it is preferred to keep the temperature for a period of time. The length of this heat preservation time will affect the density of the final opaque quartz glass. The longer this heat preservation time, the lower the density of the final opaque quartz glass, and the shorter this heat preservation time, the greater the density of the final opaque quartz glass. In the preparation method of the present invention, after the temperature is raised to 1740-1900°C, it is preferred to keep the temperature for 5-20 minutes, such as 8 minutes, 10 minutes, 15 minutes, etc. That is, in some embodiments, the preparation method of the opaque quartz glass described in [1] can be kept at 1740-1900°C for 5-20 minutes to allow the quartz sand to reach the melting temperature and sinter.
[0034] In some embodiments, the method for preparing the opaque quartz glass described in [1] can heat the temperature to 1740-1900°C at a rate of 0.2-1°C / s and keep the temperature for 5-20 minutes, so that the quartz sand reaches the melting temperature and is sintered.
[0035] In the preparation method of the present invention, the final cooling rate will affect the transparency of the final opaque quartz glass product. Reducing the cooling rate can reduce the transmittance of the final opaque quartz glass and increase the opacity of the final opaque quartz glass. Increasing the cooling rate will increase the transmittance of the final opaque quartz glass and reduce the opacity of the final opaque quartz glass. In the preparation method of the present invention, it is preferred to cool at a rate of no more than 2°C / s to obtain the opaque quartz glass.
[0036] In some preferred embodiments, the method for preparing the opaque quartz glass described in [1] can cool the temperature at a rate of 0.2 to 2°C / s.
[0037] In some embodiments, in the method for preparing the opaque quartz glass described in [1], the cooling end point can be room temperature to obtain the opaque quartz glass.
[0038] In some embodiments, the method for preparing the opaque quartz glass described in [1] can use a graphite crucible to hold quartz sand and place it in the induction heating furnace. Furthermore, an anti-sticking layer can be provided between the graphite crucible and the quartz sand. The anti-sticking layer has high temperature resistance and can be provided by coating, placement, etc.
[0039] [2] Opaque quartz glass prepared according to the preparation method described in [1].
[0040] In some embodiments, the density of the opaque quartz glass of the present invention is 0.9 to 2.19 g / cm 3 , and further can be 1.1 to 2.19 g / cm 3 , for example 1.138 g / cm 3 , 1.327g / cm 3 , 1.417g / cm 3 , 1.719g / cm 3 , 1.883g / cm 3 , 1.964g / cm 3 , 1.990g / cm 3 , 2.141g / cm 3 wait.
[0041] In some embodiments, the bubble size of the opaque quartz glass of the present invention is 1 to 300 μm, and further can be 10 to 200 μm.
[0042] In some embodiments, when the opaque quartz glass of the present invention has a thickness of 2 mm, the transmittance in the 380-3000 nm band is less than 20%, and may further be less than 8%.
[0043] In some embodiments, when the opaque quartz glass of the present invention has a thickness of 5 mm, the transmittance in the 380-3000 nm band is less than 3%, and may further be less than 2%.
[0044] In some embodiments, the hardness of the opaque quartz glass of the present invention is 1000-6900 MPa, and can further be 1700-6900 MPa.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The density of the opaque quartz glass prepared by the present invention can be between 0.9 and 2.19 g / cm 3 The quartz glass products can be adjusted within a certain range. They are easy to process and can meet the high physical and chemical stability required for biological implantation. The microporous structure in the opaque quartz glass can also provide a substrate for the growth of biological factors.
[0047] The present invention adopts an induction heating method to prepare opaque quartz glass, which solves the high hydroxyl problem caused by hydrogen-oxygen flame sintering. At the same time, only quartz sand is used as a raw material to ensure the purity of the glass matrix. The product prepared using high-purity quartz sand as the raw material can be applied to semiconductor process flows. In addition, the method requires a short heating time, has a fast preparation speed, and has low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The transmittance spectra of 2 mm opaque quartz glass samples of Example 1#, Example 2#, Example 3#, and Example 4# of the present invention are shown.
[0049] Figure 2 This is a photo of a 2 mm slice of Example 3# of the present invention.
[0050] Figure 3 The transmittance spectra of 5 mm opaque quartz glass samples of Examples 3# and 6# of the present invention are shown. DETAILED DESCRIPTION
[0051] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0052] Embodiment 1#:
[0053] First, quartz sand raw materials with a particle size of 80-100 meshes are placed in a vacuum drying oven for heating and drying at a temperature of 100°C for 24 hours; 30 g of the dried quartz sand raw materials are weighed and placed in a graphite crucible, and the graphite crucible containing the raw materials is subjected to ultrasound at a frequency of 40 kHz for 4 hours; the graphite crucible containing the raw materials is placed in an induction heating furnace and melted in an argon atmosphere, and the heating program is as follows: from room temperature to 400°C at a rate of 1°C / s, kept warm for 5 minutes, and continued at a rate of 1°C / s Raise the temperature to 800℃, keep it warm for 5 minutes, then raise it to 1000℃ at 0.8℃ / s, keep it warm for 10 minutes; then, raise it to 1480℃ at a heating rate of 0.48℃ / s, keep it warm for 5 minutes to preheat the quartz sand; then slowly raise the temperature to 1690℃ at a rate of 0.042℃ / s to heat the quartz sand evenly; then quickly raise the temperature to 1750℃ at a heating rate of 0.33℃ / s, keep it warm for 10 minutes, so that the quartz sand quickly reaches the melting temperature and sintering; finally, lower it to room temperature at 1℃ / s. During the melting process, the protective atmosphere pressure is maintained at 55000Pa. After the end, opaque quartz glass is obtained, and its density is measured to be 1.417g / cm 3 After cutting, grinding and polishing, a 2mm thick sample was obtained with a hardness of 3231MPa and a bubble size distribution of 30 to 170μm. The transmittance spectrum of the sample was obtained as follows: Figure 1 shown.
[0054] Example 2#:
[0055] First, quartz sand raw materials with a particle size of 80-100 meshes are placed in a vacuum drying oven for heating and drying at a drying temperature of 150°C for 20 hours; 30 g of the dried quartz sand raw materials are weighed and placed in a graphite crucible, and the graphite crucible containing the raw materials is subjected to ultrasonic treatment at an ultrasonic frequency of 40 kHz for 2 hours; the graphite crucible containing the raw materials is placed in an induction heating furnace and melted in an argon atmosphere, and the heating program is as follows: from room temperature to 500°C at a rate of 1°C / s, and kept warm for 5 min, then increase the temperature to 1000℃ at 0.8℃ / s and keep it for 10min; then increase the temperature to 1490℃ at a rate of 0.49℃ / s and keep it for 5min to preheat the quartz sand; then slowly increase the temperature to 1700℃ at a rate of 0.052℃ / s to heat the quartz sand evenly; then quickly increase the temperature to 1740℃ at a rate of 0.27℃ / s and keep it for 10min to make the quartz sand quickly reach the melting temperature and sinter; finally, reduce the temperature to room temperature at 2℃ / s. During the melting process, the protective atmosphere pressure is maintained at 50000Pa. After the end, opaque quartz glass is obtained, and its density is measured to be 1.719g / cm 3 After cutting, grinding and polishing, a 2mm thick sample was obtained. The hardness is 5389MPa, and the bubble size distribution is 40-130μm. The transmittance spectrum of the sample obtained by testing is as follows Figure 1 shown.
[0056] Embodiment 3#:
[0057] First, quartz sand raw materials with a particle size of 80-100 mesh are placed in a vacuum drying oven for heating and drying at a drying temperature of 100°C for 15 hours; 40g of the dried quartz sand raw materials are weighed and placed in a graphite crucible, and the graphite crucible containing the raw materials is subjected to ultrasonic treatment at an ultrasonic frequency of 20kHZ for 5 hours; the graphite crucible containing the raw materials is placed in an induction heating furnace and melted in an argon atmosphere. The heating program is to increase the temperature from room temperature to 800°C at a rate of 1°C / s and keep warm for 10m in, then increase the temperature to 1000℃ at a rate of 0.5℃ / s and keep it for 20 minutes; then, increase the temperature to 1510℃ at a rate of 0.51℃ / s and keep it for 10 minutes to preheat the quartz sand; then slowly increase the temperature to 1700℃ at a rate of 0.067℃ / s to heat the quartz sand evenly; then quickly increase the temperature to 1740℃ at a rate of 0.30℃ / s and keep it for 10 minutes to make the quartz sand quickly reach the melting temperature and sinter; finally, reduce the temperature to room temperature at a rate of 0.7℃ / s. During the melting process, the protective atmosphere pressure is maintained at 35000Pa. After the end, opaque quartz glass is obtained, and its density is measured to be 1.964g / cm 3 , after cutting, grinding and polishing, a 2 mm thick sample was obtained. Figure 2The hardness is 5846MPa, the bubble size distribution is 30-120μm, and the transmittance spectrum of the sample is as follows: Figure 1 At the same time, the sample with a thickness of 5 mm was cut, ground and polished, and the transmittance spectrum of the sample was tested as shown in Figure 3 shown.
[0058] Embodiment 4#:
[0059] First, quartz sand raw materials with a particle size of 80-120 mesh are placed in a vacuum drying oven for heating and drying at a drying temperature of 130°C for 24 hours; 35 g of the dried quartz sand raw materials are weighed and placed in a graphite crucible, and the graphite crucible containing the raw materials is subjected to ultrasonic treatment at a frequency of 40 kHz for 7 hours; the graphite crucible containing the raw materials is placed in an induction heating furnace and melted in an argon atmosphere, and the heating program is as follows: from room temperature to 400°C at a rate of 0.5°C / s, kept warm for 5 minutes, and continued at 0.8°C / s. / s to 800℃, keep warm for 5min, then increase to 1000℃ at 0.8℃ / s, keep warm for 10min; then, increase to 1500℃ at 0.48℃ / s, keep warm for 5min to preheat the quartz sand; then slowly increase the temperature to 1700℃ at a rate of 0.067℃ / s to heat the quartz sand evenly; then quickly increase the temperature to 1740℃ at a rate of 0.3℃ / s, keep warm for 10min, so that the quartz sand quickly reaches the melting temperature and sintering; finally, reduce to room temperature at 0.9℃ / s. During the melting process, the protective atmosphere pressure is maintained at 45000Pa. After the end, opaque quartz glass is obtained, and its density is measured to be 1.883g / cm 3 After cutting, grinding and polishing, a 2mm thick sample was obtained with a hardness of 5671MPa and a bubble size distribution of 60 to 100μm. The transmittance spectrum of the sample was obtained as follows: Figure 1 shown.
[0060] Example 5#:
[0061] First, quartz sand raw materials with a particle size of 80-200 meshes are placed in a vacuum drying oven for heating and drying at a drying temperature of 150°C for 12 hours; 50 g of the dried quartz sand raw materials are weighed and placed in a graphite crucible, and the graphite crucible containing the raw materials is subjected to ultrasonic treatment at a frequency of 30 kHz for 5 hours; the graphite crucible containing the raw materials is placed in an induction heating furnace and melted in an argon atmosphere, and the heating program is to increase the temperature from room temperature to 400°C at a rate of 0.5°C / s and maintain the temperature at 400°C. The temperature was raised to 1000℃ at a rate of 0.5℃ / s for 10 minutes, and then raised to 1400℃ at a rate of 0.6℃ / s for 15 minutes to preheat the quartz sand. The temperature was then slowly raised to 1710℃ at a rate of 0.002℃ / s to allow the quartz sand to be heated evenly. The temperature was then quickly raised to 1750℃ at a rate of 0.4℃ / s for 5 minutes to allow the quartz sand to quickly reach the melting temperature and sinter. The temperature was finally lowered to room temperature at a rate of 2℃ / s. The protective atmosphere pressure was maintained at 60000Pa during the melting process. After the melting process, opaque quartz glass was obtained, and its density was measured to be 1.327g / cm 3 After cutting, grinding and polishing, a 2mm thick sample was obtained with a hardness of 2554MPa and a bubble size distribution of 30 to 160μm. The test showed that the transmittance of the sample was less than 1% in the 300 to 3800nm band.
[0062] Embodiment 6#:
[0063] First, quartz sand raw materials with a particle size of 100-120 meshes are placed in a vacuum drying oven for heating and drying at a drying temperature of 100°C for 24 hours; 25 g of the dried quartz sand raw materials are weighed and placed in a graphite crucible, and the graphite crucible containing the raw materials is subjected to ultrasonic treatment at a frequency of 40 kHz for 6 hours; the graphite crucible containing the raw materials is placed in an induction heating furnace and melted in an argon atmosphere, and the heating program is as follows: from room temperature to 400°C at a rate of 1°C / s, kept warm for 5 minutes, and continued at a rate of 1°C / s Raise the temperature to 800℃, keep it warm for 10 minutes, then raise it to 1000℃ at 0.8℃ / s, keep it warm for 10 minutes; then, raise it to 1510℃ at a heating rate of 0.5℃ / s, keep it warm for 8 minutes to preheat the quartz sand; then slowly raise the temperature to 1700℃ at a rate of 0.067℃ / s to heat the quartz sand evenly; then quickly raise the temperature to 1740℃ at a heating rate of 0.27℃ / s, keep it warm for 8 minutes, so that the quartz sand quickly reaches the melting temperature and sintering; finally, lower it to room temperature at 1.2℃ / s. During the melting process, the protective atmosphere pressure is maintained at 50000Pa. After the end, opaque quartz glass is obtained, and its density is measured to be 1.990g / cm 3After cutting, grinding and polishing, a 2mm thick sample was obtained, with a hardness of 5893MPa and a bubble size distribution of 40 to 125μm. The test results show that the transmittance of the sample is less than 7% in the 300 to 3800nm band. At the same time, a 5mm thick sample was obtained by cutting, grinding and polishing, and the transmittance spectrum of the sample was tested as follows: Figure 3 shown.
[0064] Example 7#:
[0065] First, quartz sand raw materials with a particle size of 40 to 80 meshes are placed in a vacuum drying oven for heating and drying at a drying temperature of 120°C for 10 hours; 50 g of the dried quartz sand raw materials are weighed and placed in a graphite crucible, and the graphite crucible containing the raw materials is subjected to ultrasonic treatment at a frequency of 30 kHz for 5 hours; the graphite crucible containing the raw materials is placed in an induction heating furnace and melted in an argon atmosphere, and the heating program is 1°C / min from room temperature to 100°C. s to 1000℃, keep warm for 30min; then, heat it up to 1400℃ at a rate of 0.40℃ / s, keep warm for 10min to preheat the quartz sand; then slowly heat it up to 1710℃ at a rate of 0.041℃ / s to heat the quartz sand evenly; then quickly heat it up to 1760℃ at a rate of 0.5℃ / s, keep warm for 15min, so that the quartz sand quickly reaches the melting temperature and sintering; finally, cool it down to room temperature at 1℃ / s. During the melting process, the protective atmosphere pressure is kept at 20000Pa. After the end, opaque quartz glass is obtained, and its density is measured to be 1.138g / cm 3 After cutting, grinding and polishing, a 2mm thick sample was obtained with a hardness of 1771MPa and a bubble size distribution of 40 to 200μm. The test showed that the transmittance of the sample was less than 1% in the 300 to 3800nm band.
[0066] Example 8#:
[0067] First, quartz sand raw materials with a particle size of 180-200 mesh are placed in a vacuum drying oven for heating and drying at a drying temperature of 130°C for 24 hours; 40 g of the dried quartz sand raw materials are weighed and placed in a graphite crucible, and the graphite crucible containing the raw materials is subjected to ultrasonic treatment at a frequency of 20 k HZ, the ultrasonic time is 5h; the graphite crucible containing the raw materials is placed in an induction heating furnace and melted under an argon atmosphere. The heating program is to increase the temperature from room temperature to 300℃ at 1℃ / s, keep it warm for 5min, continue to increase it to 500℃ at 1℃ / s, keep it warm for 10min, then increase it to 1000℃ at 0.8℃ / s, keep it warm for 5min; then, increase it to 1490℃ at a heating rate of 0.49℃ / s, keep it warm for 15min to preheat the quartz sand; then slowly increase the temperature to 1680℃ at a rate of 0.19℃ / s to heat the quartz sand evenly; then quickly increase the temperature to 1740℃ at a heating rate of 0.45℃ / s, keep it warm for 10min, so that the quartz sand quickly reaches the melting temperature and sinters; finally, decrease it to room temperature at 1℃ / s. During the melting process, the protective atmosphere pressure was maintained at 75000Pa. After the melting, opaque quartz glass was obtained. Its density was measured to be 2.141g / cm 3 After cutting, grinding and polishing, a 2mm thick sample was obtained with a hardness of 5970MPa and a bubble size distribution of 10 to 60μm. The test showed that the transmittance of the sample was less than 8% in the 300 to 3800nm band.
[0068] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing opaque quartz glass, characterized in that: include: Use an induction heating furnace, the atmosphere in the furnace is a protective atmosphere that does not participate in the reaction, and the protective atmosphere pressure is 10000~90000Pa; The quartz sand is placed in the induction heating furnace, first heated to 1400-1570° C. to preheat the quartz sand; then heated to 1650-1710° C. at a rate not exceeding 0.2° C. / s to uniformly heat the quartz sand; then heated to 1740-1900° C. at a rate not less than 0.2° C. / s to make the quartz sand reach the melting temperature and sinter; finally cooled at a rate not exceeding 2° C. / s to obtain opaque quartz glass.
2. The preparation method according to claim 1, characterized in that: The protective atmosphere includes a nitrogen atmosphere and / or a rare gas atmosphere; In the preparation method, the total heating time does not exceed 5 hours.
3. The preparation method according to claim 1, characterized in that: The quartz sand is dried before being placed in the induction heating furnace; The quartz sand is first subjected to ultrasonic and / or vibration operation before being placed in the induction heating furnace; The size of the quartz sand placed in the induction heating furnace is 40-200 meshes.
4. The preparation method according to claim 1, characterized in that: After the quartz sand is placed in the induction heating furnace, the temperature is first raised to 1400-1570° C. at a rate of not less than 0.3° C. / s to preheat the quartz sand; Furthermore, after the quartz sand is placed in the induction heating furnace, it is first heated to 1000° C. at a rate of not less than 0.3° C. / s and kept warm for 5 to 30 minutes, and then heated to 1400 to 1570° C. at a rate of 0.3 to 0.6° C. / s and kept warm for 3 to 30 minutes to preheat the quartz sand.
5. The preparation method according to claim 1, characterized in that: The temperature is increased to 1650-1710°C at a rate of 0.002-0.2°C / s.
6. The preparation method according to claim 1, characterized in that: Raise the temperature to 1740-1900°C at a rate of 0.2-1°C / s and keep warm for 5-20 minutes to make the quartz sand reach the melting temperature and sinter.
7. The preparation method according to claim 1, characterized in that: The temperature is lowered at a rate of 0.2 to 2°C / s, and the end point of the cooling is room temperature, thereby obtaining opaque quartz glass.
8. The preparation method according to claim 1, characterized in that: A graphite crucible is used to hold quartz sand and is placed in the induction heating furnace; An anti-sticking layer is provided between the graphite crucible and the quartz sand.
9. Opaque quartz glass prepared according to the preparation method according to any one of claims 1 to 8.
10. The opaque quartz glass according to claim 9, characterized in that: The density of the opaque quartz glass is 0.9-2.19 g / cm 3 , further 1.1~2.19g / cm 3 The bubble size is 1 to 300 μm, further 10 to 200 μm. When the thickness is 2 mm, the transmittance in the 380 to 3000 nm band is less than 20%, further less than 8%. When the thickness is 5 mm, the transmittance in the 380 to 3000 nm band is less than 3%, further less than 2%. The hardness is 1000 to 6900 MPa, further 1700 to 6900 MPa.
Citation Information
Patent Citations
Preparation method of quartz lead
CN109160724A
Production method of high-quality opaque quartz glass ingot
CN111233309A
Preparation method of high-purity low-hydroxyl quartz glass raw material
CN111393022A
High-purity opaque quartz glass ingot and preparation method thereof
CN117303719A
Opaque silica glass and the production process therefor
EP0728709A1
Cited By
Preparation method of bubble-free low-expansion quartz glass
CN119874168A
Preparation method of bubble-free low-expansion quartz glass
CN119874168B
Graphite crucible coating process, coated graphite crucible and application thereof
CN120536866A